Epidemiology of psychological development disorders in adolescents: use of alcohol and other drugs - Fábio Vinícius Rocha; Roberto Lazzarini de Oliveira; Daniella Almeida Silva Brum; Ricardo Bezerra Cavalcante; Richardson Miranda Machado (Rev Rene)
Objective: to identify the personal and clinical characteristics of adolescents alcohol and other drugs’ users with Psychological Development Disorders.  Methods: this retrospective study analyzes the care of the Psychosocial Care III Center. Results: from the 415 adolescents treated, 52.3% were female; 89.9% were between 12 to 14 years old, 51.6% attended by court order, 28.2% had “Unspecified Disorder of Psychological Development”; 32.3% used multiple drugs. Being between 12 and 14 years of age meant 2.5 and 1.5 times more risk of having Psychological Development Disorders, respectively. Cocaine/crack users were more likely (4.27 times) to receive the diagnosis of “Psychoactive Substance Use.” Conclusion: adolescents are treated in accordance with the law, which requires treatment for social living inadequacies due to high use of cannabinoids, and there is a difficulty of professionals in treating Psychological Development Disorders.